Assessment of the Immune Responses Induced in Cattle after Inoculation of a Mycobacterium bovis Strain Deleted in Two mce2 Genes - Blanco, Federico Carlos (2012)
The generation of efficient candidate vaccines against bovine tuberculosis will contribute to the control of this zoonotic disease. Rationally attenuated Mycobacterium bovis strains generated by knockout of virulence genes are promising candidate vaccines. However, to be effective, these candidate vaccines should at least maintain the immunological properties of their virulent parental M. bovis strains. Therefore, the aim of this study was to obtain an M. bovis strain deleted in the mce2 genes and evaluate the effect of the mutation on the immunological profile elicited by the bacteria in cattle. We showed that the activation of CD4+ T cells in cattle inoculated with the mutant strain was equivalent to that in animals inoculated with the parental strain. Moreover, after in vitro stimulation, peripheral blood mononuclear cells from animals inoculated with the mutant produced higher levels of mRNA Th-1 cytokines than the parental strain. Therefore, these results indicate that the mce2 mutant is a promising candidate vaccine against bovine tuberculosis.